The Effect of Selected Factors on the Intensity of Low-back Pain within Six Months from the Complaint Onset - Małgorzata Kołpa; Agnieszka Jankowicz-Szymańska; Edyta Mikołajczyk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Low-back pain (LBP), resulting from a slipped disc, exerts a long-lasting and irritating impact on all aspects of human life. Aim. The study aimed at assessing the effect of selected factors on the severity of pain measured on the Visual Analogue Scale (VAS) in patients who were treated conservatively due to a slipped disc in the lumbar section of the spine. Material and Methods. A total of 400 patients of the Outpatient Neurosurgical Clinic at the St. Lukas Regional Hospital in Tarnow, Poland, were involved in the survey. The observations (weight status and pain intensity) were conducted twice: when the problems appeared and after 6 months. Results. Obese and overweight individuals (79.5%) and the ones with android adiposity (86%) were most numerously represented in the research groups. The most severe low-back and leg pain in surveys one and two was reported by obese patients and the ones who belonged to the group of senior participants. Conclusions. Conservative treatment combined with pro-health instructions brought the greatest subjective pain relief. The worst effects were achieved by obese patients. (JNNN 2015;4(1):24–29)